Water Management System Based On Zero Run Off Policy In Multi Unit Area (Case Study Of Menara Asuransi Astra In Cilandak, South Jakarta, Indonesia) - Mukarromah, lailatul; Andawayanti, Ussy; Prayogo, Tri Budi (Civil and Environmental Science Journal (CIVENSE), 2018)
Water management system is an effort of planning, management, control, and supervision of runoff water that is structured and integrated in an area according with the policies. In Governor Regulation of Jakarta Capital City Administration No. 43 of 2013 on the Peil of Building Floor Licence, it is explained that the implementation of the zero Delta Q principle is to keep the runoff remain in the area up to 100% or to drain the water out of the region up to zero percent or zero runoff. In this regard, this research is expected to develop a concept of a regional water system implementation which compares the hydrological analysis method with related regulatory methods, to obtain a technical policy that can be applied in order to meet the regional regulations based on the zero delta Q or zero runoff concept for all to be developed areas in Jakarta by taking case study of South Jakarta area as a pilot project. The method used is to compare the Governor Regulation of Jakarta as the reference in zero run off calculation with the Indonesian National Standard Regulation (SNI) No. 03 2453 2002 on the Procedure of Planning Technique of Rainwater Recharge wells for Grounds using hydrological and hydraulics analysis. The conclusion is the calculation by hydrological analysis in accordance with the Indonesian National Standard Regulation (SNI) No. 03 2453 2002 on the Procedure of Planning Technique of Rainwater Recharge wells for Grounds becomes the chosen method, because it has a more detailed result and zero runoff concept can be met, so the runoff at the study site did not increase the load of Grogol River.